1977
DOI: 10.1017/s0021932000023828
|View full text |Cite
|
Sign up to set email alerts
|

The chance of conception during lactation

Abstract: Many mothers in low-income countries, particularly in rural areas, nurse their children for 1–2 years on the average. The main purpose of this practice is, of course, to provide the newborn child with the nutrition necessary for its survival. Prolonged breast-feeding, however, also has a birth-spacing effect and postpones the next pregnancy by inhibiting ovulation and by delaying resumption of the menstrual cycle. Suckling of the infant is important for this suppression of the menstrual cycle because it leads … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1981
1981
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…Since a successful parturition is followed by an interval of lactation that may extend into the next breeding season, it may be that the reduction in pregnancy rate at the second year, which again is more pronounced for the earlymaturing females, may be due to the effects of the lactational period following first pregnancy. There is evidence from studies on human females that prolonged lactation does delay the next ovulation (Knodel, 1977;Van Ginneken, 1977). Since rhesus monkeys are seasonal breeders, a failure to conceive during one mating season imposes a 12-month interval to subsequent ovulation.…”
Section: Discussionmentioning
confidence: 99%
“…Since a successful parturition is followed by an interval of lactation that may extend into the next breeding season, it may be that the reduction in pregnancy rate at the second year, which again is more pronounced for the earlymaturing females, may be due to the effects of the lactational period following first pregnancy. There is evidence from studies on human females that prolonged lactation does delay the next ovulation (Knodel, 1977;Van Ginneken, 1977). Since rhesus monkeys are seasonal breeders, a failure to conceive during one mating season imposes a 12-month interval to subsequent ovulation.…”
Section: Discussionmentioning
confidence: 99%
“…The ultimate test of fertility is pregnancy and several reports have demonstrated that breast feeding increases the interval between pregnancies (for summary, see van Ginneken, 1977). For example, two studies compared the time to next conception in nursing and non-nursing mothers from Alaskan Eskimo (Berman, Hanson & Hellman, 1972) and rural Indian populations (Potter, New, Wyon & Gordon, 1965).…”
Section: Methods Of Assessing Lactational Infertilitymentioning
confidence: 99%
“…The significance of breast-feeding as a method of contraception was studied in rural Zambia by Wenlock (1977), who noted that breast-feeding has a contraceptive effect and that the peak of new conceptions occurred between 25 and 27 months postpartum. Carballo (1977) stated that the potential role of lactational amenorrhoea as a child-spacing mechanism should not be underestimated, and he contended that postpartum lactational amenorrhoea, though it does not offer complete protection against conception for individual mothers, is of value when a whole community is considered, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Introduction of breast milk substitutes into babies' diets adversely affects the duration of postpartum amenorrhoea. Lactational amenorrhoea is very long only if breast-feeding is complete, successful and unsupplemented (Jelliffe & Jelliffe, 1972;Van Ginneken, 1977). In some parts of Central Africa the positive contraceptive effects of the factors mentioned above on postpartum lactational amenorrhoea are further reinforced by sexual abstinence (Rosa, 1975;Mosley, Osteria & Huffman, 1977).…”
Section: Introductionmentioning
confidence: 99%